PENGGUNAAN KARYA CIPTA PROGRAM KOMPUTER OJEKBINTARO OLEH PT. GOTO GOJEK TOKOPEDIA,TBK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA: The Use of Computer Program Copyright Works Ojekbintaro by PT. Goto Gojek Tokopedia, Tbk Based On Law Number 28 Of 2014 On Copyright - Alshafa Cinta Aquarianto; Simona Bustani (Faculty of Law, Universitas Trisakti, 2025)
A computer program is considered a form of creative work protected by copyright law. With the rapid development of technology, it has become easier for plagiarism of creative works to occur. One notable case of copyright dispute involving computer programs is the copyright dispute between Hasan Azhari, the creator of the Ojek Bintaro computer program, and PT. Goto Gojek Tokopedia, Tbk. In this case, the method of ordering an online motorcycle taxi through the Gojek application was found to have substantial similarities with the Ojek Bintaro computer program created by Hasan Azhari. The identification problem discussed in this article are whether the use of the Gojek application infringes the copyright of the creator of the Ojek Bintaro computer program (http://ojekbintaro.blogspot.com) based on Law No. 28 of 2014 on Copyright. This research employs a normative legal research method with a descriptive nature and is analyzed qualitatively, with conclusions drawn based on a deductive reasoning pattern. The result and conclusion indicates that the use of the Gojek application infringes the copyright of the creator of the Ojek Bintaro computer program, as the model for the Ojek Bintaro online motorcycle taxi program was established earlier in 2008, before Gojek was founded in 2010.